(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
This article talks about the history of the origin and formation of medical terms. It contains information on the use of the initially formed naming of medical terms in today’s consumption, their importance, and their use as interdisciplinary terms.